Cover Feature: Measurement of Protein Dynamics from Site Directed Cu(II) Labeling (Anal. Sens. 1/2023). Issue 1 (26th October 2022) - Singewald, Kevin; Hunter, Hannah; Cunningham, Timothy F.; Ruthstein, Sharon; Saxena, Sunil
Abstract : The cover feature image illustrates two sites of a protein with different site specific reorientational dynamics (purple). Such differences can be measured by newly developed site‐directed Cu(II) labeling methodology. The resultant EPR lineshape at physiological temperatures is sensitive to the timescale of backbone motion. Importantly, this methodology enables site‐specific detection on both α‐helices and β‐sheets via EPR. Thus, the role of protein dynamics to protein function can be elucidated. More information can be found in the Review by Sunil Saxena and co‐workers .